RANCANG BANGUN SISTEM INFORMASI REKRUTMEN KARYAWAN PADA PT. MITRANIAGA CIPTASOLUSI BERBASIS WEB - Fauziyah Fauziyah; Rifka Irhamna; Alexius Ulan Bani (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Employees are one of the most important components in an organization or company in order to make the best contribution to a company. PT. Mitraniaga Ciptasolusi is a company engaged in personnel consulting, requiring human resources (employees) who are not only competent. but also can survive and compete with human resources (employees) of other companies. Employee recruitment carried out at PT. Mitraniaga Ciptasolusi currently still uses the conventional method in the sense that the employee recruitment process still uses the old method in each process, this is considered to be still lacking in effectiveness and efficiency. For the method of designing and developing an employee recruitment system, namely by using Unfield Modeling Language (UML), the programming language uses PHP and MySQL as the database. The method used in building this application is the System Development Life Cycle (SDLC) method which has stages, namely planning, analysis, design, implementation, use. With this employee recruitment system, it can help actors in every process in determining new employees to be accepted in the company.